2022
DOI: 10.3390/agriculture12050584
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intensive Youth Participation in Agriculture on Rural Households’ Revenue: Evidence from Rice Farming Households in Nigeria

Abstract: The youth unemployment situation is an essential component of the current agricultural policy agenda of the Federal Government of Nigeria. Deep-rooted debates on finding a lasting solution to this problem using agriculture have been targeted as one of the panaceas. Using data from 207 systematically selected rice-producing households, this study employed the Propensity Score Matching method (PSM) and the Inverse Probability Weighted Regression Adjustment method (IPWRA) to examine the effect of intensive youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…This is due to the fact that increase in years of farming experience increases with the age of the farmers and as they grow older due to the increase in age their level of participation decreases. This is contrary to the findings of James et al (2022) which found years of farming experience were positive and significantly influenced the decision to participate in agriculture.…”
Section: The Factors Influencing Youth Participation In Maize Productioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is due to the fact that increase in years of farming experience increases with the age of the farmers and as they grow older due to the increase in age their level of participation decreases. This is contrary to the findings of James et al (2022) which found years of farming experience were positive and significantly influenced the decision to participate in agriculture.…”
Section: The Factors Influencing Youth Participation In Maize Productioncontrasting
confidence: 99%
“…The study found out that access to credit was positively associated with youth participation in maize production at 1% probability level. The positive effect of access to credit on youth participation in maize production which is contrary with the finding of James et al (2022) indicated that access to credit decreases the livelihood of youth deciding to engage in agriculture intensively and it is in line with the findings of Attamah, Aguh & Agwu (2023) which revealed that lack of access to credit increases the chances of youth's involvement in rice production. In the same vein amount of credit, had positive relationship with participation of youth in maize production, amount of credit is another motivating factor for youth's participation in maize production as it boosts access to inputs, its availability could determine the extent of youths' production capacity.…”
Section: The Factors Influencing Youth Participation In Maize Productionsupporting
confidence: 52%
“…However, the impact does not reach the acceptable statistical significance level of 5 percent precision level because the precision level P=0.177. The positive association between age and farm income levels aligns with other scholars like [29][30][31][32][33][34] who posit that as age increases, the level of income of farmers engaged in vertically integrated markets also increase. This entails that the younger the person become, the lower the likelihood of falling into higher farm income level.…”
Section: Youthfulness Impact On Farm Income Level In Vertically Integ...supporting
confidence: 85%
“…Likewise, a study in Nigeria by [31] demonstrate that youth farmers who participate in agriculture program outperform those who do not in farm productivity and well-being. Another study in Nigeria by [32] show that production and revenue are positively influenced by intensive youth participation in agriculture. These studies in Nigeria entails that youthfulness have a positive outcome on farm productivity and farm income.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…However, the extent to which youth contribute to households' welfare has gained little or no research attention despite a huge literature on rural youths (Adeyanju et al, 2021;Akrong & Kotu et al, 2022;Arslan et al, 2021a;Arslan et al, 2021a;Barsoum et al, 2017;Fasakin et al, 2022;Fawole et al, 2019;Ibrahim et al, 2021;Ng'atigwa et al, 2020;Osabohien et al, 2020;Osabohien et al, 2021;Rufai et al, 2021). Recent studies on rural households' welfare focus on the level of welfare (Donath et al, 2021;Delesalle, 2021).…”
Section: Introductionmentioning
confidence: 99%